2018
DOI: 10.2174/1381612823666170926133843
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular Adipose Tissue as an Endocrine Organ: The Role of Statins

Abstract: Adipose tissue (AT), aside from being an energy storage site, functions as a source of cytokines, adipokines and other vasoactive molecules. Dysfunctional AT contributes to the development of cardiovascular disease by shifting to a pro-oxidant, pro-inflammatory phenotype. Perivascular AT (PVAT) is of particular importance to the development of vascular disease, due to its close proximity to the vascular wall. Molecules released from PVAT can exert both pro- and anti-contractile effects, the balance of which pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…There was a significant increase in white adipose tissue, which can significantly increase adipokine secretion [14,48,49]. Adiponectin, which is one of the adipokines, has a variety of physiological activities that are beneficial to the body, such as restoring insulin to normal and preventing arteriosclerosis and cardiovascular diseases [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…There was a significant increase in white adipose tissue, which can significantly increase adipokine secretion [14,48,49]. Adiponectin, which is one of the adipokines, has a variety of physiological activities that are beneficial to the body, such as restoring insulin to normal and preventing arteriosclerosis and cardiovascular diseases [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…For example, down-regulation of miR-543 alleviates insulin resistance by targeting the SIRT1 58 , miR-27a induces insulin resistance by repressing PPARγ 59 , and miR-27b and miR-130a were linked to adipocyte insulin resistance by targeting the insulin receptor itself 12 , 14 , 60 . Adipose tissue is not only an organ for storing fat and energy, but also an important endocrine organ 61 . We found that, compared to WT mice fed a HFD, miR-125b-2KO mice fed a HFD had significantly slower glucose recovery after injection with glucose or insulin, indicating that miR-125b-2 plays a role in glucose tolerance and insulin sensitivity in vivo.…”
Section: Discussionmentioning
confidence: 99%